PENGARUH PENURUNAN TEGANGAN BATERAI TERHADAP EFISIENSI KOMPONEN SWITCHING PADA PENERAPAN APLIKASI BLDC MOTOR CONTROLLER - Audrey Devi Anggraeni; Waru Djuriatno; Muhammad Aswin (Jurnal Mahasiswa TEUB, 2023)
3-Phase Inverter is a type of electronic device that converts a DC voltage source into a 3-Phase AC voltage source, which there are 6 switching components works alternately are used as input power in the operation of a BLDC Motor. MOSFET is a type of switching components that is usually used because it has high efficiency at low voltage levels and has advantages at high switching speeds. The purpose of this study is to design and simulate a system to determine the effect of a decrease in battery voltage on the resulting losses which affect the efficiency of the switching in the speed control applications of BLDC Motor Controller. The test was carried out by simulating a circuit to control the speed of BLDC Motor in one battery discharge cycle using the MATLAB Simulink application. In this test, the State of Chargae (SoC) is recorded, the voltage and current are generated by the battery, the VDS and IDS flowing through the MOSFET, also the results of PIN and POUT. Recording is done in a range of SoC values of 100%, 80%, 60%, 40%, and 20%. Speed control on BLDC Motors is designed using a controller that has feedback with a setpoint of 200 RPM. Based on the results of the testing the voltage drop due to power consumption in the operation of the BLDC Motor, obtained an increase in losses in the switching components. So that the voltage drop is inversely proportional to the losses of the switching components, and the greater the power dissipation generated, the efficiency of the switching components will decrease. Index terms : MOSFET, SoC, Power Dissipation, Efficiency, BLDC Motor